Marginal-covert moult in the House Sparrow Passer domesticus. Issue 2 (3rd July 2021) - Guallar, Santi; Carrillo-Ortiz, José; Quesada, Javier
ABSTRACT: Marginal coverts are often neglected in passerine moult studies due to their small size and large number. Here, we document eight moult components of this group of wing coverts in a House Sparrow population from Barcelona in 2018–21: timing, growth rate, intensity, speed, duration, sequence, extent and barb density. We also tested the influence of various intrinsic and extrinsic factors on marginal-covert moult. Our adult population started marginal-covert moult on 29 July and finished it on 29 August, with the moult of hatch-year birds delayed 13 days in relation to the moult of adults. Growth rate of the largest marginal covert increased significantly with its size but did not differ between sexes. Intensity of marginal-covert moult replacement was not constant during the moult progress, which took 32 days on average. Moult sequence of marginal coverts started with the proximal feathers, proceeded distally replacing the central rows and was completed toward the front and rear rows. Moult extent was complete except in one case. Size of the largest marginal covert increased with calamus width, but not significantly, and barb density decreased with feather size, but not significantly, and neither measure differed between sexes. Comparison with published results indicated that growth rate is lower in marginal coverts than in primaries and rectrices, whereas barb density is greater. Linear regression of marginal-covert size on both growth rate and barb density can be used to predict growth rate and barb density of flight feathers in the House Sparrow.